2013
DOI: 10.1037/a0031851
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative causal model theory of conditional reasoning.

Abstract: The authors propose and test a causal model theory of reasoning about conditional arguments with causal content. According to the theory, the acceptability of modus ponens (MP) and affirming the consequent (AC) reflect the conditional likelihood of causes and effects based on a probabilistic causal model of the scenario being judged. Acceptability of MP is a judgment of causal power, the probability that the antecedent cause is efficacious in bringing about the consequent effect. Acceptability of AC is a judgm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
88
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(102 citation statements)
references
References 52 publications
(105 reference statements)
6
88
0
3
Order By: Relevance
“…Despite Stenning and van Lambalgen (2005) themselves proposing that suppression effects might be dealt with by causal Bayes nets, actual attempts to model these inferences using CBNs have only just begun (Fernbach & Erb, 2013). Sloman and Lagnado (2005) and Ali, Chater, and Oaksford (2011) both looked at conditional inference and CBNs but not explicitly at the classical suppression effects (but see, Oaksford & Chater, 2013).…”
Section: The Probabilistic Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite Stenning and van Lambalgen (2005) themselves proposing that suppression effects might be dealt with by causal Bayes nets, actual attempts to model these inferences using CBNs have only just begun (Fernbach & Erb, 2013). Sloman and Lagnado (2005) and Ali, Chater, and Oaksford (2011) both looked at conditional inference and CBNs but not explicitly at the classical suppression effects (but see, Oaksford & Chater, 2013).…”
Section: The Probabilistic Approachmentioning
confidence: 99%
“…In establishing this point we will present some arguments that causal 7 Bayes nets (CBNs) can provide a good framework within which to develop a theory of conditional reasoning and we show that CBNs can naturally account for these patterns of inference (Ali, Chater, & Oaksford, 2011;Fernbach & Erb, 2013;Oaksford & Chater, 2007, 2013.…”
Section: However Recently Stenning and Van Lambalgen (2005) Have Promentioning
confidence: 99%
“…They found that ratings of the likelihood of disablers explains additional variance in predicting the inferences participants endorse, e.g., MP, over and above the sheer number of disablers generated. This experiment appears to replicate Fernbach and Erb (2013) where participants estimated disabling strength and the base rate of disablers to compute causal power in a noisy-OR gate. For each retrieved disabler, the disabling probability can then be calculated as disabling strength × base rate.…”
Section: Enablers Vs Alternative Causes (3)mentioning
confidence: 89%
“…For instance, according to one line of research on conditional reasoning, mental models can be tagged with probability information (e.g., Barrouillet, Gauffroy, & Lecas, 2008;Johnson-Laird, Legrenzi, Girotto, Legrenzi, & Caverni, 1999). Some research suggests that for causal conditionals, those mental models could be mental causal models (Ali, Chater, & Oaksford, 2011;Fernbach & Erb, 2013). Accordingly, causal reasoning with mental causal models of the acquired causal structure that allows for the incorporation of probabilistic evidence (Krynski & Tenenbaum, 2007;Meder et al, 2014;Waldmann & Hagmayer, 2013) could produce the diversity effect.…”
Section: Discussionmentioning
confidence: 99%